Differential impact of antiretroviral therapy initiated before or during pregnancy on placenta pathology in HIV-positive women. (1st April 2021) - Ikumi, Nadia M.; Malaba, Thokozile R.; Pillay, Komala; Cohen, Marta C.; Madlala, Hlengiwe P.; Matjila, Mushi; Anumba, Dilly; Myer, Landon; Newell, Marie-Louise; Gray, Clive M.
Abstract : Objective: To examine the association between timing of antiretroviral treatment (ART) initiation in HIV-infected women and placental histopathology. Design: A nested substudy in a larger cohort of HIV-infected women which examined the association between ART status and birth outcomes. Methods: Placentas ( n  = 130) were examined for histopathology from two ART groups: stable ( n  = 53), who initiated ART before conception and initiating ( n  = 77), who started ART during pregnancy [median (interquartile range) 15 weeks gestation (11–18)]. Using binomial regression we quantified associations between ART initiation timing with placental histopathology and pregnancy outcomes. Results: One-third of all placentas were less than 10th percentile weight-for-gestation and there was no significant difference between ART groups. Placental diameter, thickness, cord insertion position and foetal–placental weight ratio were also similar by group. However, placentas from the stable group showed increased maternal vascular malperfusion (MVM) (39.6 vs. 19.4%), and decreased weight (392 vs. 422 g, P  = 0.09). MVM risk was twice as high [risk ratios 2.03 (95% confidence interval: 1.16–3.57); P  = 0.01] in the stable group; the increased risk remaining significant when adjusting for maternal age [risk ratios 2.04 (95% confidence interval: 1.12–3.72); P  = 0.02]. Furthermore, MVM was significantly associated with preterm delivery and low birth weight ( P  = 0.002 and <0.0001, respectively). Conclusion: Preconception initiation of ART was associated with an increased MVM risk, and may contribute to placental dysfunction. The association between MVM with preterm delivery and low birth weight suggests that a placenta-mediated mechanism likely links the putative association between long-term use of ART and adverse birth outcomes. Abstract : Supplemental Digital Content is available in the text